Tuberculosis: Laboratory Diagnosis and Treatment Strategies - McHugh, Timothy D (2014)
Tuberculosis is a disease of poverty aﬀ ecting adults in their most productive years. In 2010, there were 8.8 million incident cases with 1.1 million tuberculosis deaths in patients not infected with HIV. A further 0.35 million deaths were associated with HIV-positive patients (WHO, 2011). These ot -quoted ﬁ gures demonstrate the challenge that tuberculosis control presents and this book highlights the state of the art in the mainstays of tuberculosis control: laboratory diagnosis and treatment. Tuberculosis control is a multifaceted problem, but positive identiﬁ cation of the tubercle bacillus and assessment of its drug susceptibility are essential components in the strategy. It is telling that in 2010, 8 out of 22 high-burden countries did not meet the benchmark of 1 microscopy unit per 100,000 population. Furthermore, in a combined list of 36 countries that were high-burden countries and/or high MDR-TB burden countries, 20 had less than the benchmark of one laboratory capable of culture and drug sensitivity testing per 5 million population (WHO, 2011). It is hoped that the rational approach to conventional testing and roll-out of novel technologies described here will serve to provide cost-eﬀ ective and robust technologies that will improve delivery of diagnostic services in resource-poor set ings. For many years, there was stasis in the development of drugs for the treatment of tuberculosis. The HIV pandemic and, more recently, the development of MDR- and XDR-TB (and indeed now TDR-TB) have changed our perspective. New drugs are being developed and our approaches to evaluating them require review. The spectrum of this activity is outlined in chapters covering the fundamental biology of drug action (Chapters 12 and 13), as well those focused on clinical trial methodology (Chapters 10, 11 and 15). I have included three examples of approaches to new drug development; the ATC compounds (Chapter 16) represent a design-based approach in which the ATC scaﬀ old is designed to inhibit the fat y acid synthase pathway. By comparison, Chapters 17 and 18 discuss repurposing established drugs: in Chapter 17 the rifamycins are revisited and Chapter 18 discusses how the imperative of MDR-TB has driven the reconsideration of thioridazine. Of course, matching these developments are exciting developments in vaccine design and these are captured in Chapter 19.